Expansion of logistics infrastructure in the oil sector as a form of improving Poland's energy security - Dominik Piękoś; Przemysław Suduł; Sławomir Augustyn (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2023)
Energy security refers to a country’s ability to provide stable access to energy, including energy resources such as oil. In Poland, PKN Orlen and PERN S.A. are the key companies managing oil logistics and processing for public and private use. A special purchaser of petroleum substances is the Armed Forces of the Republic of Poland, which are a fundamental element of the State Defense System, which use the acquired fuels to ensure the effective implementation of state defense and security policies.